Customer value co-creation and reuse intention on mobile banking platform - Dewandono, Titus Nugrahadi; Agus, Anna Amalyah (Universitas Hayam Wuruk Perbanas, 2023)
This study seeks to investigate how emotional attachment influences both customer value co-creation and reuse intention in the context of mobile banking. The relationship is examined with the mediating role of engagement in mobile banking quality. Employing a quantitative approach, the study targets mobile banking users in Indonesia. Data collection involves distributing Likert scale-based questionnaires through Google Forms, utilizing convenience sampling. The analysis utilizes partial least square analysis, revealing that emotional attachment significantly and positively impacts both customer value co-creation and reuse intention in mobile banking. Additionally, the findings indicate that engagement in mobile banking quality plays a positive mediating role in the relationship between emotional attachment and customer value co-creation, as well as reuse intention in mobile banking. The practical implication for mobile banking providers is to focus on maintaining the existing quality of mobile banking services while enhancing brand image to support consumer reuse intention and value co-creation. Future research could explore more representative sampling methods and incorporate additional variables that may influence the relationship between emotional attachment and customer value co-creation, as well as reuse intention in mobile banking.